Dream yoga and the practice of natural light - Nam-mkhavi-nor-bu (Snow Lion Publications, 2002)
The nature and classes of dreams -- The practice of the night -- The methods of practicing the essence of dreams -- The illusory body -- The essential practice of clear light -- Dreams of clarity -- The methods of transference -- The pilgrimage to maratika -- An interview with Chögyal Namkhai Norbu -- The Buddha no farther than one's palm -- A brief biography of Chögyal Namkhai Norbu